Correlation between haemoglobin concentration and oxygen saturation (SpO2) in elderly professors - Della Aprilliana Suherlim*; Hikmat Permana; Leonardo Lubis (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
The aging process is recognized by the decreases of the body functions which is caused by molecular and cellular damages. The population which is mostly affected by this aging process is elderly. In elderly, it is most likely that tissue oxigenation decreases due to the reduction of haemoglobin level and oxygen saturation (SpO2).This study aimed to evaluate  the correlation between the hemoglobin concentration and SpO2 in the elderly professors in Universitas Padjadjaran (UNPAD), Bandung. This was cross sectional study using secondary data from medical records of the elderly professors. One hundred and eight data of the professors (84 males and 24 females) who met the inclusion and exclusion criteria were used in this study.Spearman’s Rank correlation test was used to analyze the data of total subjects and male professors group, while Pearson correlation test was used to analyze the data of female professors group. Correlation test between hemoglobin concentration and SpO2 resulted in an insignificant results in male professors (r = 0.028; p = 0.801), female professors (r = 0.132; p = 0.538), and total subjects (r = 0.036; p = 0.712).  In conclusion, there is no correlation between hemoglobin concentration and SpO2 in the elderly professors of UNPAD, Bandung.